Influence of Aswaja-Based Moderate Islamic Values Internalization on Students’ Religious Attitudes at Jember Islamic University - Prima Cristi Crismono; Hengki Hartono; Mahnawawe Yakoh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Religious polarization and intolerance among youth continue to rise globally, including in Indonesia, where survey data from institutions such as BNPT and several national studies show increased exposure of university students to exclusive and extreme religious narratives. This condition highlights the strategic urgency of strengthening religious moderation in Islamic higher education, particularly through frameworks rooted in Ahlus Sunnah wal Jama’ah (Aswaja), which emphasize tawassuth, tawazun,tasamuh, and i‘tidal. Despite growing attention to religious moderation, empirical quantitative evidence linking the internalization of Aswaja-based values to students’ religious attitudes remains limited, especially within Indonesian Islamic universities. Addressing this gap, the present study analyzes the influence of Aswaja-based moderate Islamic value internalization on students’ religious attitudes at Universitas Islam Jember. Using a quantitative explanatory design with 155 randomly selected students, data were collected through a five-point Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression. The findings show that both the internalization of Aswaja values and students’ religious attitudes are in the high category. Regression analysis indicates a positive and significant effect of Aswaja value internalization on religious attitudes (β = 0.63, p < 0.001), with a determination coefficient of 40%. These results provide empirical evidence that deeper internalization of Aswaja values contributes substantially to more moderate, inclusive, and balanced religious attitudes. The study reinforces the importance of integrating Aswaja-based value education as an effective strategy for promoting religious moderation within Islamic higher education institutions.